Facing the Challenges of Film Production:From Economic Uncertainty to Digital Era Sustainable Practices - Melati Kusuma Wardhani, S.I.Kom, M.I.Kom, Melati Kusuma Wardhani, S.I.Kom, M.I.Kom (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2025)
The film business has numerous significant difficulties among economic uncertainty and growing need for sustainable practices. Especially in the digital era, this research seeks to underline these problems and investigate creative ideas that might be used. Using literature research to examine several works on the difficulties and creative advances in film production, the hired approach is qualitative. The findings show that although encouraging sustainable practices, the acceptance of new technologies such artificial intelligence (AI) and virtual reality (VR) could satisfy changing audience needs and enhance manufacturing efficiency. Thus, cooperation among government agencies, local producers, distributors, and platform providers determines the future expansion and viability of the film industry.